The real business of ancient Maya economies : from farmers' fields to rulers' realms - Masson, Marilyn A.; Freidel, David A.; Demarest, Arthur Andrew (Maya studies., 2020)
"A timely synthesis of the latest research and perspectives on ancient Maya economics, this volume illuminates the sophistication and complexity of economic systems in the Preclassic, Classic, and Postclassic periods. Fully representing the range of current views on the subject, these essays delve deeply into multiple facets of a complex, interdependent material world"--